Effects of lactulose and other laxatives on ileal and colonic pH as measured by a radiotelemetry device. Issue 12 (December 1974) - Bown, R. L.; Gibson, J. A.; Sladen, G. E.; Hicks, B.; Dawson, A. M.
Abstract : Using a pH-sensitive radiotelemetering device the effect of lactulose on luminal pH in the ileum, colon, and rectum has been compared with that of two other laxative agents. Lactulose produced marked acidification of proximal colonic contents but this effect was not consistently maintained into the distal colon. Sodium sulphate acidified distal rather than proximal colonic contents. However, for a similar degree of laxation it was not possible to produce a significantly more uniform reduction of pH along the length of the colon by combining these laxatives compared with lactulose alone. Magnesium sulphate had little effect upon luminal pH except in the rectum where a significant rise occurred. These results are discussed in relation to both normal colonic physiology and to their possible relevance to the treatment of chronic hepatic encephalopathy by colonic acidification.